Reading the figural, or, Philosophy after the new media - Rodowick, David Norman (Post-contemporary interventions., 2001)
Theorizes the concept of the figural as a way to get beyond the long held aesthetic distinction between plastic and linguistic arts, a distinction that will not work for film and new media.